Experience of telemedicine use in a big cohort of patients with rheumatoid arthritis during COVID-19 pandemic (2021)
We have read with interest the work of Bozzalla-Cassione et al1 published recently in your journal regarding the implementation of a telemedicine programme for patients with lupus in northern Italy. It is logical to suppose that the risk of patients with rheumatic diseases of having a more severe clinical course if they become infected with the COVID-19 infection is very high; however, although some of the reports show that there seems to be a low incidence of COVID-19 infection in patients with rheumatic disease, collaborative work with large cohorts is needed, which could show us the real incidence of COVID-19 infection in these patients and what happens with the establishment of telemedicine programmes.2–6 We show an experience in a specialised centre in Bogota, Colombia; currently, we have a cohort of 5597 patients with rheumatoid arthritis (RA) in exclusively ambulatory care. On 12 March 2020, in Colombia, the health emergency by COVID-19 was established and a week later the Ministry of Health ordered the outpatient care procedure for the population in isolation. From that moment on, our institution, carrying out the proper logistical and legal processes, proceeded to convert its ambulatory care services into care through telemedicine.